2020
DOI: 10.1177/0032885520978476
|View full text |Cite
|
Sign up to set email alerts
|

Does the Experience of Imprisonment Affect Optimism About Reentry?

Abstract: Desistance research has linked prison inmate expectations with positive outcomes after release, but very little research addresses what makes them optimistic about their future. Using data from a representative sample, this article analyzes whether the manner in which a prison sentence is served impacts expectations about reentry. Results show that experiencing harsh prison conditions makes incarcerees more pessimistic about reentry, while receiving family support during imprisonment has the opposite effect. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Maintaining a sound support system from inside and outside prison is crucial to ensure inmates adhere to rehabilitation programs and transition for re-entrance to the community. Researchers believe that seeking social support is a form of coping that reduces psychological distress in prisons (Cid et al, 2020; Luke et al, 2020). A meta-analysis and systematic review on the effect of social support on depression among inmates showed that it provides protection from depression (Gariepy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining a sound support system from inside and outside prison is crucial to ensure inmates adhere to rehabilitation programs and transition for re-entrance to the community. Researchers believe that seeking social support is a form of coping that reduces psychological distress in prisons (Cid et al, 2020; Luke et al, 2020). A meta-analysis and systematic review on the effect of social support on depression among inmates showed that it provides protection from depression (Gariepy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%